Health status and demand for health care of the rural women: preliminary observations from the backward districts of Karnataka state, South India - Lakshmi, S. Jyothi; Shivakumarswamy (International Journal Of Community Medicine And Public Health, 2023)
Background: In the last few decades, rural people’s health care has garnered increased attention. Especially rural women are facing a variety of life-threatening diseases as a result of traditional health culture, gender-based health exclusion, and low socioeconomic status. This study attempted to disclose the health status and demand for health care of rural women in two backward districts of Karnataka state- south India. Methods: The study has used a survey and interview methods of data collection from 426 rural women from two districts of Karnataka. Results: This study found that women reaching menopause state face a slew of health issues; including anemia (44%), stress (63%) menstrual irregularities (39%), heart disease (47%), arthritis (50%), and diabetes (48%) from a low socio-economic profile. Women in the menopausal stage are the most impacted, followed by pre-menopause and reproductive groups. Per-capita income, level of education, and medical expenditure are decisive factors in the demand for quality health care. Conclusions: Changing health culture has a close nexus with the socioeconomic status affecting rural health behaviour of women. Household income and occupation have a key role in determining women’s health. It is time to establish low-cost healthcare insurance for rural women and encourage the medical pluralism that exists in rural areas.